Socialization of Aerobic Kids Exercise with PAUD Laboratory School UN PGRI Kediri in 2019 - Puspodari; Sugito; M. Akbar Husein Allsabah; Setyo Harmono; Weda; M. Yanuar Rizky; Wing Prasetya Kurniawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
Sports is one form of activity to improve the physical quality of humans. Many ways to develop physical motor skills of one of them with aerobic exercise. Aerobic Kids Gymnastics is a type of rhythmic gymnastics whose movements are adjusted to the age and development of a Paud child. The movements of dancing, jumping, spinning like mimicking animal movements make pre-school-aged children more eager to follow it. From the characteristics of sports for early childhood, the author tries to package in the form of aerobic kids gymnastics that are fun so that children feel interested to follow and have fun. The assumption that gross motor development will develop automatically with increasing age of the child, is a false assumption. The development of gross motor skills in children needs the assistance of educators in early education institutions, namely in terms of what is helped. Aerobic Kids gymnastics is done directly by doing a demonstration of Aerobic Kids gymnastics in learning sports. The subjects of this study were PAUD Laboratory School students of PGRI Kediri and teachers. The results of this activity showed that there was good enthusiasm from students and teachers in participating in the Aerobic Kids Gymnastics Movement.